Multivariate shifting mean plus persistence model for simulating the Great Lakes net basin supplies - Sveinsson, Óli Grétar Blöndal, author; Salas, Jose D., author; Colorado State University, publisher (Colorado State University. Libraries, 2006)
The focus of this paper is to develop a multivariate model for modeling the annual net basin supplies (NBS) of the Great Lakes. Not all NBS series show similar behavior. For example, a feature that is apparent in some but not all NBS series is a sudden shifting pattern. In this paper previous studies of univariate shifting mean models are expanded to develop multivariate contemporaneous shifting mean models. These multivariate models are further mixed with CARMA models in such a way, that the lag zero correlation in space is conserved between the underlying processes of the different models. The full contemporaneous shifting mean CARMA models are successfully applied for modeling jointly the whole Great Lakes system, preserving the spatial correlation at lag zero between different lakes, and preserving other important statistical characteristics of the individual lakes.
Hydrology days 2006
AGU hydrology days 2006
2006 annual AGU hydrology days was held at Colorado State University on March 20 - March 22, 2006.